Isosolo as a Space for Aesthetics and Cultural Identity in Ayapo Village Papua - Chirstian Lamban Gasong; Nanik Sri Prihatini; Branckly. E. Picanussa (Universitas Negeri Medan, 2025)
Traditional Papuan music is not merely a form of entertainment but serves as a medium of cultural expression, spirituality, and collective identity. One tradition that embodies this complexity is *Isosolo* in Ayapo Village, Jayapura, a practice of singing and dancing on decorated boats that reflects the deep interconnection between humans, nature, and spirituality in a unique aesthetic form. This study employs a qualitative approach within the framework of ethnomusicology and cultural anthropology, drawing on performance documentation, interviews with local cultural figures, and relevant literature. The findings reveal that the aesthetic values of Isosolo manifest in three main dimensions: audial, visual, and kinesthetic. The sound of the tifa drum, conch shell, and collective singing construct an acoustic landscape that is not only sonically beautiful but also reinforces social solidarity, cultural identity, and ecological awareness. The decorated boat as a floating stage, combined with communal dance movements, affirms the Sentani people’s close relationship with the lake as their living space. Isosolo’s audial aesthetics emerge as a holistic experience that is communal, relational, and contextual, where music transcends sound to function as a medium of transmitting values, symbols, and spirituality. The uniqueness of this study lies in its focus on the audial and collective dimensions of Isosolo, which have rarely been examined in depth, while its novelty lies in the integration of classical, pragmatic, and contemporary aesthetic theories to interpret Isosolo as an epistemological space connecting humans, culture, and nature. Thus, this study enriches the global discourse on non-Western musical aesthetics and reaffirms Isosolo as a living cultural heritage to be preserved and passed on across generations.